2019
DOI: 10.2147/ott.s176700
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pancreatic cancer in young adults: changes, challenges, and solutions</p>

Abstract: Despite improvements in multidisciplinary treatments, survival of pancreatic cancer (PC) patients remains dismal. Studies dealing with early onset pancreatic cancer (EOPC) patients are scarce. In this review, we discuss differences between EOPC and late-onset pancreatic cancer based on findings in original papers and reviews with a focus on morphology, genetics, clinical outcomes and therapy. In conclusion, families with a positive history of PC and patients with BRCA 1 or 2 mutations should be monitored. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 85 publications
(116 reference statements)
0
16
1
Order By: Relevance
“… 9 It is important to consider patients with early onset pancreatic cancer, as they may be able to undergo more intensive therapy due to their better overall health. 9 …”
Section: Discussionmentioning
confidence: 99%
“… 9 It is important to consider patients with early onset pancreatic cancer, as they may be able to undergo more intensive therapy due to their better overall health. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Likely also related to therapeutic advances are the improvements in survival among AYAs with lung, liver, pancreas, and stomach carcinomas (more prominent in males) [ 64 , 65 , 66 , 67 ]. Nevertheless, survival outcomes for these cancers in AYAs have remained relatively poor (<60%), which is characteristic for these cancer types regardless of patient age [ 52 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, different molecular classification has been proposed thanks to the introduction of high-throughput techniques and the better knowledge of the pathogenetic role of the PDAC-related genes KRAS, TP53, SMAD4 , and CDKN2A . 66 Based on the molecular characteristics of PDAC, several authors conducted an interesting molecular classification approach that we summarised below. The molecular classification by Collisson et al 67 identified subtypes of PDAC which are different for outcomes and therapeutic response ( Table 3 ): classical, quasi-mesenchymal, and exocrine-like.…”
Section: Histopathology and Molecular Pathwaysmentioning
confidence: 99%
“…Comparing the gene signatures of the abovementioned classification, it can be observed a non-perfect overlap. As well reported by Primavesi et al 66 several working groups used different terminologies as well as different approaches to define biological-similar subtypes and, the definition of consensus genetic models among different classifications is desirable to find new diagnostic and tailored treatment options.…”
Section: Histopathology and Molecular Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation